2020
DOI: 10.5114/aoms.2020.98364
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of urologic emergency visits and admissions during the COVID-19 pandemic: a retrospective, multicenter, nationwide study

Abstract: Introduction: We aimed to examine the change in the number and severity of visits to the emergency departments (EDs) and subsequent admissions for urgent urologic conditions in the early stage of the coronavirus disease 2019 (COVID-19) pandemic in Poland. Material and methods: We evaluated data from 13 urologic centers in Poland and compared the number of visits to the EDs and subsequent admis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
(33 reference statements)
0
17
2
1
Order By: Relevance
“…Given the huge drop in outpatient cystoscopy (77%) after the COVID-19 outbreak revealed in the Uro-SoMe survey [11], the detection of primary and recurrent urothelial cancer was likely to be altered also in Poland. Considering inpatients, on the other hand, a drop in haematuria cases presenting as urological emergencies could at that moment be as high as 25% [14]. When compared to the 35% mean decrease in surgeries for RCC declared by responders of the UroSoMe survey [11] or the 53% decline reported in the recent EAU survey [17], the 11.7% reduction observed in our study cannot be considered more than moderate.…”
Section: Discussioncontrasting
confidence: 60%
“…Given the huge drop in outpatient cystoscopy (77%) after the COVID-19 outbreak revealed in the Uro-SoMe survey [11], the detection of primary and recurrent urothelial cancer was likely to be altered also in Poland. Considering inpatients, on the other hand, a drop in haematuria cases presenting as urological emergencies could at that moment be as high as 25% [14]. When compared to the 35% mean decrease in surgeries for RCC declared by responders of the UroSoMe survey [11] or the 53% decline reported in the recent EAU survey [17], the 11.7% reduction observed in our study cannot be considered more than moderate.…”
Section: Discussioncontrasting
confidence: 60%
“…Our findings support several recent reports. In their multicenter study, Rajwa et al found no differences in the laboratory parameters of 3883 patients with renal colic, hematuria, or urinary retention between the 2020 pandemic and 2019 reference periods in Poland (16). In a comparison of patient's characteristics before any restrictions and during the severe lockdown, no differences were found in levels of creatinine, Hb, CRP, and WBC.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of SARS-CoV-2 infection is equal in both sexes; however, disease severity and progression rates are approximately three times higher in the male gender [1][2][3]. This sex-specific discrepancy can potentially be explained by the mechanism of SARS-CoV-2 entry into human host cells.…”
Section: Introductionmentioning
confidence: 99%